ANALISIS AKTIVA PAJAK TANGGUHAN DAN AKRUAL SEBAGAI PREDIKTOR MANAJEMEN LABA: KAJIAN EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEJ - Suranggane, Zulaikha (Jurnal Akuntansi dan Keuangan Indonesia, 2007)
Pernyataan Standar Akuntansi Keuangan (PSAK) No 46 about income tax accounting in Indonesia, allows for management to judge deferred tax assets valuation annually in the financial statements. This regulation can give management an opportunity to use the deferred tax assets account to manage earnings. The probability of earnings management can be predicted by many variables. How a manager manages earnings in this study are by controlling accrual, and deferred tax assets valuation allowance under PSAK No 46. This research is purposed to investigate whether discretionary accrual modified Jones Model and deferred tax assets valuation allowance can be used to predict earnings management to prevent loss. Data used in this research are collected from audited-annual financial statements of manufacturing firms listed in the Jakarta Stock Exchange 2003-2005 The sampling method is purposive sampling. There are 66 samples to be analyzed by logistic regression. The results show that discretionary accruals can be used to predict earnings management, and the other hand, the deferred tax assets valuation allowance can not. The limitation and the research implication are also discussed.